2008
DOI: 10.1128/jvi.01545-07
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Viremia Induces Plasmacytoid Dendritic Cell Activation In Vivo and Diminished Alpha Interferon Production In Vitro

Abstract: Human immunodeficiency virus type 1 (HIV-1) infection has been associated with perturbations of plasmacytoid dendritic cells (PDC), including diminished frequencies in the peripheral blood and reduced production of type I interferons (IFNs) in response to in vitro stimulation. However, recent data suggest a paradoxical increase in production of type 1 interferons in vivo in HIV-infected patients compared to uninfected controls. Using a flow cytometric assay to detect IFN-α-producing cells within unseparated pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
97
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 66 publications
(60 reference statements)
10
97
2
1
Order By: Relevance
“…In addition, a strong increase in pDC density in the T cell zone in lymph nodes of asymptomatic HIV-infected patients was reported in an earlier study (37). Furthermore, it has been recently shown that pDCs are indeed chronically stimulated in HIV-infected patients and produce type I IFNs, which in turn contributes to their hyporesponsiveness to subsequent in vitro stimulation, probably through a negative regulatory feedback mechanism (38). Viral activation of pDCs can be regulated by either of the two TLRs, TLR7 or TLR9, which are considered to be the receptors that human and mouse pDCs use for recognition of RNA/retroviruses (39) and DNA (40), respectively.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, a strong increase in pDC density in the T cell zone in lymph nodes of asymptomatic HIV-infected patients was reported in an earlier study (37). Furthermore, it has been recently shown that pDCs are indeed chronically stimulated in HIV-infected patients and produce type I IFNs, which in turn contributes to their hyporesponsiveness to subsequent in vitro stimulation, probably through a negative regulatory feedback mechanism (38). Viral activation of pDCs can be regulated by either of the two TLRs, TLR7 or TLR9, which are considered to be the receptors that human and mouse pDCs use for recognition of RNA/retroviruses (39) and DNA (40), respectively.…”
Section: Discussionmentioning
confidence: 88%
“…[18][19][20] Third, pDCs became unresponsive to secondary stimulation once the acute IFN-I response was over, suggesting that they were desensitized for IFN-I production in vivo as observed previously for human pDCs in vitro after primary stimulation with Toll-like receptor-9 ligand 41 and consistent with the reduced ability of pDCs to produce IFN-I in response to in vitro stimulation in patients infected with HIV. 42 Fourth, we did not evidence IFN-I-positive cell clusters outside the pDCs gate in our in vitro stimulation studies.For the first time, our study monitored the acute transient burst of IDO activity in parallel with acute changes in pDCs dynamics and IFN-I concentration in the early phase of viremia. The kinetic of IDO activity in cynomolgus macaques in our study and the positive correlation observed between IDO activity and viral load are consistent with observations made in Indian rhesus macaques.…”
mentioning
confidence: 93%
“…on May 10, 2018. by guest www.bloodjournal.org From in vitro production of IFN-I in patients infected with HIV. 42 As IFN-I became undetectable soon after its concentration peaked in the plasma, despite the persistence of high viral loads in our study, we compared the capacity of pDCs to respond to SIV and HSV-1 stimulation before and after this peak, to evaluate a possible refractory phase in vivo.In vitro, cynomolgus macaque pDCs underwent rapid IFN-␣ synthesis in response to SIV stimulation ( Figure 5A), as previously shown in response to HSV stimulation. 24 These cells were also characterized extensively by flow cytometry ( Figure S3).…”
mentioning
confidence: 99%
“…Significantly, a higher level of IRF7 RNA in ART naïve viremic subjects is in discrepancy with lower IFNα production by these subjects. There is some recent evidence which suggests that IFNα production is high in vivo in HIV infected progressors but a combination of feedback inhibition and prior direct activation through TLRs by HIV RNA leads to diminished ex-vivo IFNα production upon exposure to CpG-A or HIV particles [45]. While the IRF7 gene expression was assessed in terms of its mRNA abundance in the peripheral blood of the subjects, the IFNα levels were based on an in vitro stimulation assay, the two parameters could not be correlated and may be the reason of this discrepancy.…”
Section: Discussionmentioning
confidence: 99%